2015
DOI: 10.5812/hepatmon.26818
|View full text |Cite
|
Sign up to set email alerts
|

Association of Tumor Necrosis Factor-alpha Polymorphisms and Risk of Coronary Artery Disease in Patients with Non-alcoholic Fatty Liver Disease

Abstract: Background:Cardiovascular events account for the main cause of death in patients with non-alcoholic fatty liver disease (NAFLD), and are largely influenced by genetic factors. Although multiple studies showed that tumor necrosis factor-alpha (TNF-α) polymorphisms are risk factors in the progression of NAFLD, few papers on the association of the polymorphisms and the developing coronary artery disease (CAD) in NAFLD patients have been reported.Objectives:The present study was designed to evaluate the associatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 41 publications
1
17
0
2
Order By: Relevance
“…This is in accordance with the study by Cheng et al conducted to evaluate the association of TNF-α polymorphisms with the risk of developing coronary artery disease (CAD) in NAFLD patients, which also reported that NAFLD patients without CAD who were carriers of the GA genotype had higher serum triglycerides levels compared to those with the GG genotype (p = 0.017) [48].…”
Section: Discussionsupporting
confidence: 90%
“…This is in accordance with the study by Cheng et al conducted to evaluate the association of TNF-α polymorphisms with the risk of developing coronary artery disease (CAD) in NAFLD patients, which also reported that NAFLD patients without CAD who were carriers of the GA genotype had higher serum triglycerides levels compared to those with the GG genotype (p = 0.017) [48].…”
Section: Discussionsupporting
confidence: 90%
“…The complete full texts of the remaining 89 articles were assessed, excluding 64 articles that did not meet the study inclusion criteria. Reasons for exclusion of these studies were theoretical research [3], lack of clinical outcomes [10], duplicate articles [5], and lack of a control group [11]. We ultimately identified a total of 25 case-control studies that met the inclusion criteria for this meta-analysis, including 7697 patients in the CAD group and 9655 in the control group.…”
Section: Overview Of Included Studiesmentioning
confidence: 99%
“…TNF-α -308 GA heterozygote genotype was positively associated with elevated levels of TG in NAFLD patients with CAD. Then obtained the conclusion that TNF-α -308 GA genotype plays a crucial role in the development of CAD in NAFLD patients [ 93 ].…”
Section: Tumor Necrosis Factors-alpha Gene ( Tnf-α mentioning
confidence: 99%